Changes in PYY and gastric emptying across the phases of the menstrual cycle and the influence of the ovarian hormones. (1st December 2016) - Campolier, Marta; Thondre, Sangeetha Pariyarath; Clegg, Miriam; Shafat, Amir; Mcintosh, Ali; Lightowler, Helen
Abstract: Nutrition-related studies avoid the participation of pre-menopausal women due to the potential effect of the menstrual cycle (MC) on their appetite regulation. It is generally accepted that women increase their energy intake during the luteal phase (LPh) compared to the follicular (FPh), however what happens in the menstrual phase (MPh) and how this might be regulated remains uncertain. Although some research indicates changes in the gastric emptying (GE) velocity, whether PYY is affected by the MC phase, remains unknown. The aim of this study was to assess whether eating the same breakfast in each of the three MC phases would change the GE time, the PYY response and post-prandial satiety such that they might affect subsequent food intake. Furthermore, the aim was to associate any potential differences to the fluctuations in estradiol (E2 ) and progesterone (P4 ) within a MC. Nine naturally cycling women attended to the laboratory to consume a standardised breakfast on three occasions, each of them representing one of the MC phases. Breath samples to measure GE time, plasma samples to quantify PYY levels and hunger scores were collected for a total of 4 h after which food intake was assessed by an ad-libitum buffet lunch. GE and PYY levels changed significantly across the phases of the MC (p < 0.05). GE was correlated to P4 and E2 -P4 ratio (r = −0.5 and 0.4, respectively). To conclude, the appetite regulators PYY and GE time change depending upon the MC phases with GE time associated with the ovarian hormone levels which suggests the necessity of controlling the MC phase in studies looking at the appetite response.